TRANSMISSION ANALYSIS OF TWO DIMENSION OPTICAL GRATING STRUCTURE - Wisely, Nick
A structural analysis of optical devices becomes a necessity to support the development of modern technology, this is because the structure of optical devices will determine the unique ability of devices to manipulate light. One interesting structure to be reviewed is the 1-dimensional periodic lattice structure. Besides being a relatively simple in structure, this structure also has many applications such as light filters, and Bragg mirrors. However, the process of making one-dimensional optical lattice is often not optimal, this is because the manufacturing process is carried out layer by layer. In addition, additional media can arise due to interactions between layered media, material that is not completely attached, and in certain methods can cause damage to the medium. This Final Project research will review another alternative structure which is also simple namely two-dimensional optical lattice. With the effective refractive index approach, the two-dimensional optical lattice transmittance curve will be analytically reviewed using the matrix transfer method. In further analysis an optimization will be carried out in the range of the passband in order to obtain a at transmittance curve.